Integrating Telegram in English class to elevate speaking performance and engagement: A classroom action research in junior high school - Sholichah, Innas Shofiatus; Wahjuningsih, Eka; Puspa, Areta; Imamyartha, David (Journal on English as a Foreign Language, 2025)
Albeit the vast integration of mobile technologies into English classrooms at junior high schools, measures to elevate speaking performance through mobile instant messaging, such as Telegram, remains scant. Addressing this void, this classroom action research (CAR) aimed to enhance students' speaking fluency and accuracy by using Telegram as a tool for speaking tasks. A group of eighth-grade students was chosen based on the preliminary noting their struggled with speaking skills and the issues concerning low learning engagement. This research operationalized mobile technology and communicative language learning tasks in two cycles, each of which involved two meetings and one meeting of a speaking test. Research data were collected from the speaking test and observation. Descriptive statistics revealed the improvement of students' speaking proficiency from the first to the second cycle, 35% and 48%, respectively. The speaking task was also successful in amplifying students' engagement, where 61% of them were actively engaged in the second cycle, compared to 57% in the first cycle. This research exhibited how Telegram mediated supportive and engaging authentic speaking tasks even for beginner learners. Research implications underscore the potency of Telegram for transforming speaking practice as a challenging experience into an inviting and personalized learning endeavor.